Gastropods from the Cretaceous-Palaeogene boundary in Denmark - Hansen, Thomas (Zootaxa, 2019)
Gastropods constituted one of the most successful faunal groups in the Danish Basin around the Cretaceous-Palaeogene (K-Pg) boundary, both with regard to abundance and diversity. Only 19 species were known previously; this number is here increased to 140. The end-Cretaceous Danish fauna is represented by 79 taxa of which 85 % became extinct at the boundary. A new fauna of 72 species arose within a remarkably short time interval of less than half a million years. The extinction seems to have hit rather randomly with regard to feeding strategies, while geographical range stands out as the single most important factor in survivorship. The succeeding speciation was controlled by changes in substrate and food availability, where non-carnivores and taxa dependent on a hard substrate were replaced by hunting carnivores and mud-adapted taxa in response to the disappearance of the Cretaceous bryozoan mounds. The gastropod genus Loxotoma Fischer, 1885 is renamed as Palaeoloxotoma nom. nov. due to its junior synonymy with a moth. 38 new species are erected. These are Acirsa torensis n. sp., Acmaea selandica n. sp., Ageria laxa n. sp., Ageria skeldervigensis n. sp., Amaea alicae n. sp., Amaea stevniensis n. sp., Amaurellina ravni n. sp., Arene jakobseni n. sp., Ataphrus (Ataphrus) knoesensis n. sp., Bathrotomaria jakobseni n. sp., Ceratia rodvigensis n. sp., Cerithiella selandica n. sp., Cerithiopsis restemlongis n. sp., Claviscala minor n. sp., Coniscala umbilica n. sp., Cranopsis cretacea n. sp., Cylichna stevniensis n. sp., Dolicholatirus lorenzi n. sp., Epalxis? rosenkrantzi n. sp., Epetrium s.l. skeldervigensis n. sp., Eucycloscala gracilicostatus n. sp., Fusinus schnetleri n. sp., Mathilda dania n. sp., Mesalia danica n. sp., Opaliopsis carlsbergi n. sp., Pseudocochlespira transversa n. sp., Pseudotoma danica n. sp., Tatara pseudosassia n. sp., Tectus? indecorus n. sp., Temnotropis stevniensis n. sp., Thereitis carlsbergi n. sp., Thereitis cretacea n. sp., Thylacodes contendis n. sp., Unitas heinbergi n. sp., Vatopsis heinbergi n. sp., Vexillum? rosenkrantzi n. sp., Vexillum tenestolidum n. sp. and Zebinella selandica n. sp.